Surface Epitope Coverage Affects Binding Characteristics of Bisphenol-A Functionalized Nanoparticles in a Competitive Inhibition Assay. (23rd November 2015) - Lu, Yang; Peterson, Joshua Richard; Luais, Erwann; Gooding, John Justin; Lee, Nanju Alice
Abstract : The biomolecule interface is a key element in immunosensor fabrication, which can greatly influence the sensor performance. This paper explores the effects of surface epitope coverage of small molecule functionalized nanoparticle on the apparent affinity (avidity) of antibody in a competitive inhibition assay using bisphenol-A (BPA) as a model target. An unconventional two-antibody competitive inhibition ELISA (ci-ELISA) using thiolated BPA modified gold nanoparticles (cysBPAv-AuNP) as a competing reagent was devised for this study. It was shown that the antibody complexation with cysBPAv-AuNPs required a minimum number of surface epitopes on the nanoparticle to form a sufficiently strong interaction and reliable detection. The binding of cysBPAv-AuNP to anti-BPA antibodies, for limited antibody binding sites, was enhanced by a greater number of epitope-modified nanoparticles (cysBPAv-AuNP) as well as with higher epitope coverage. Increasing the molar concentration of epitope present in an assay enhanced the binding between anti-BPA antibodies and cysBPAv-AuNP. This implies that, to increase the limit of detection of a competitive inhibition assay, a reduced molar concentration of epitope should be applied. This could be achieved by either lowering the epitope coverage on each cysBPAv-AuNP or the assay molar concentration of cysBPAv-AuNP or both of these factors.